2009
DOI: 10.1371/journal.pgen.1000702
|View full text |Cite
|
Sign up to set email alerts
|

Mouse HORMAD1 and HORMAD2, Two Conserved Meiotic Chromosomal Proteins, Are Depleted from Synapsed Chromosome Axes with the Help of TRIP13 AAA-ATPase

Abstract: Meiotic crossovers are produced when programmed double-strand breaks (DSBs) are repaired by recombination from homologous chromosomes (homologues). In a wide variety of organisms, meiotic HORMA-domain proteins are required to direct DSB repair towards homologues. This inter-homologue bias is required for efficient homology search, homologue alignment, and crossover formation. HORMA-domain proteins are also implicated in other processes related to crossover formation, including DSB formation, inhibition of prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
522
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(567 citation statements)
references
References 85 publications
(215 reference statements)
33
522
0
Order By: Relevance
“…Because the Cdc20-Mad2 substrate used in our assay contained p31 comet (necessary for the release of the subcomplex from MCC), TRIP13 seemed to be a likely candidate. Indeed, immunoblotting of MonoQ column fractions with anti-TRIP13 showed an exact coincidence of the peak of the elution of TRIP13 protein with that of Cdc20-Mad2 dissociating activity, with both centered in fractions [25][26] (Fig. 1B).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Because the Cdc20-Mad2 substrate used in our assay contained p31 comet (necessary for the release of the subcomplex from MCC), TRIP13 seemed to be a likely candidate. Indeed, immunoblotting of MonoQ column fractions with anti-TRIP13 showed an exact coincidence of the peak of the elution of TRIP13 protein with that of Cdc20-Mad2 dissociating activity, with both centered in fractions [25][26] (Fig. 1B).…”
Section: Resultsmentioning
confidence: 89%
“…In some instances, an AAA-ATPase can bind to different adaptor proteins, thus changing its substrate specificities and cellular functions (19). In the case of the TRIP13 AAA-ATPase and of its homologs, a role in meiotic recombination has been reported in mice, yeast, worms, and plants (25)(26)(27)(28). This function has been explained by their action to dislocate certain proteins from Recombinant Cdc20-Mad2 complex was expressed and purified as described in Materials and Methods and was added to the assay at 2 nM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third organizational axes layer is made by the HORMA-domain proteins HORMAD1 and HORMAD2. They preferentially bind to unsynapsed chromosome axes and become displaced from the AEs by synapsis formation in a TRIP13-dependent manner (Wojtasz et al 2009). A Hormad1 -/-mutant mouse model suggests that the HORMADs function in a meiotic "synapsis" checkpoint.…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 99%
“…Recently a Pch2 orthologue (TRIP13) has also been identified in mice. The analyses of these mutants revealed that TRIP13 is required for the removal of HORMAD1 from synapsed axes [34], completed homologous synapses, and DSB repair, indicating that at least some of the functions of Pch2 are conserved in mammals. However a specific role in inter-homolog vs. sister bias has not been ascertained [35].…”
Section: Interhomolog Vs Sister Biasmentioning
confidence: 99%